Stepped Augmented Glenoid Component in Anatomic Total Shoulder Arthroplasty for B2 and B3 Glenoid Pathology: A Study of Early Outcomes. (6th October 2021) - Iannotti, Joseph P.; Jun, Bong-Jae; Derwin, Kathleen A.; Ricchetti, Eric T.
Abstract : Background: Posterior glenoid bone loss is commonly associated with primary glenohumeral osteoarthritis. Surgical management of bone loss in anatomic total shoulder arthroplasty (aTSA) remains controversial. We studied the use of a stepped augmented glenoid component for management of Walch B2 and B3 glenoids and compared the radiographic and clinical outcomes at short-term follow-up with those achieved with a non-augmented component of the same design in Walch A1 glenoids. Methods: Ninety-two patients (42 A1, 29 B2, and 21 B3 glenoids) were prospectively followed after aTSA. Sequential 3-dimensional (3D) computed tomography (CT) imaging was performed preoperatively, within 3 months postoperatively with metal artifact reduction (MAR) to define implant position, and at a minimum of 2 years postoperatively with MAR. Scapular 3D registration with implant registration allowed 3D measurement of glenoid implant position, implant shift, and central peg osteolysis (CPO). Results: CPO with or without implant shift occurred in a higher percentage of B3 glenoids treated with the augmented glenoid component (29%) than A1 glenoids treated with a standard component (5%) (p = 0.028). There was no significant difference in the frequency of CPO between B2 glenoids with the augmented component (10%) and A1 glenoids with the standard component. There was no difference in postoperative glenoid component version and inclination between groups. B3 glenoids were associated with more component medialization relative to the premorbid joint line compared with A1 and B2 glenoids (p < 0.001). Conclusions: A stepped augmented glenoid component can restore premorbid glenoid anatomy in patients with asymmetric biconcave glenoid bone loss (Walch B2), with short-term clinical and radiographic results equivalent to those for patients without glenoid bone loss (Walch A1) treated with a non-augmented component. There is a greater risk of CPO in patients with moderate-to-severe B3 glenoid pathology with this stepped augmented glenoid component. Longer follow-up will help define the clinical implications of CPO over time. Level of Evidence: Therapeutic Level II . See Instructions for Authors for a complete description of levels of evidence.